2010
DOI: 10.1177/0363546509357915
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Chondrocyte Implantation

Abstract: Autologous chondrocyte implantation has emerged as an effective and durable solution for the treatment of large full-thickness cartilage and osteochondral lesions of the knee joint. Our study suggests that the clinical and functional outcomes remain high even 10 to 20 years after the implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
541
6
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(588 citation statements)
references
References 33 publications
20
541
6
12
Order By: Relevance
“…Our results agree with other published studies which have shown that ACI tissue needs time to remodel and continues to improve in quality with time 3 . However, even after 20 months the ACI repair tissue has fewer GAGs with different sulphation patterns than controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree with other published studies which have shown that ACI tissue needs time to remodel and continues to improve in quality with time 3 . However, even after 20 months the ACI repair tissue has fewer GAGs with different sulphation patterns than controls.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of patient knee function scores following ACI have indicated the importance of a two-year post-operative status as an indicator of the long term success of this treatment 2,3,9,10 . Whilst these results are reassuring there remains concern about the quality of the cartilage formed within the defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous chondrocyte implantation (ACI) is a cell-based cartilage repair technology using ex vivo cultivated chondrocytes. It has been established for the treatment of full cartilage defects of the knee joint in clinical routine with proven long-term efficacy [6]. For some years matrix associated ACI (MACI) has emerged abandoning the periosteal flap and thereby providing easier and time-saving handling [7].…”
Section: Introductionmentioning
confidence: 99%
“…The cell suspension is retained by either a patch of periosteum or a commercially available collagen membrane, sutured to the edges of the defect and sealed with fibrin. Our center has used ACI in approximately 500 procedures and we and others have shown that it has the potential to improve functional outcome [2][3][4] and generate repair tissue that offers a durable surface and is well integrated with the surrounding cartilage [5][6][7][8]. In our audits of ACI, 80% of patients improve by 15 months, and this improvement is sustained for 9-16 years [3,9].…”
mentioning
confidence: 98%